Criminal Responsibility Of Corporate Crime Towards The Criminal Act Of Illegal Fishing (Study of Verdict No. 31/Pid.Sus/2013/PTR) - Agung Tri Radityo (Legal Standing : Jurnal Ilmu Hukum, 2017)
Investigating the aspects or arresting the intellectual perpetrators of corporate crimes has not been typically done by the public prosecutor in the trial concerning the responsibility of corporate crime in criminal act of illegal fishing. Even though it has been stated clearly in law of state, the corporate crime of illegal fishing is not strictly enforced. Moreover, the criminal act of illegal fishing is considered as general crimes instead of special crimes. In this case, illegal fishing is supposed to be considered as special crimes that should be solved distinctively. This article particularly discusses the improper enforcement of corporate crime in illegal fishing conducted by law enforcement agents. Terribly, this concern would not bring deterrent effects for the perpetrators, particularly the intellectual perpetrators and their corporate.